Chronological survey of the Cyrillic manuscript books kept in Vilnius - Keršulytė, Edita (Slavistica Vilnensis, 2016)
The article aims to publish the Chronological index of the Cyrillic manuscript books kept in Vilnius made on the basis of the N. Morozova’s Catalogue Кириллические рукописные книги, хранящиеся в Вильнюсе: Каталог (2008). An analysis of the index data is proposed with a focus on the chronological order of the manuscripts and relative statistics. The chronological index contains information on 460 items (Cyrillic manuscript books and their fragments, parts, and additions) that are now kept in six different scholarly and heritage institutions in Vilnius. The time span of the manuscripts is from the second half of the XI c. to the third quarter of the XX c., most of the items (≥123) belonging to the XVI c. Most of the manuscripts have been written on paper, and only 29 items are on parchment. Merely 16.74 % of the items have specific indications concerning the time they were written, the rest of them have been approximately dated according to their paper watermarks or, in the case of parchment books and their fragments, their paleographic features.